Drawing Type: An Introduction to Illustrating Letterforms - Fowkes, Alex (Quarto Publishing Group USA, 2014)
Part inspiration and part workbook, the images of hand-drawn type will inspire and excite any designer to draw and explore type. Drawing Type features real-world projects and sketchbooks of well-known type designers, including interviews about their processes.